2007
DOI: 10.1152/ajprenal.00147.2006
|View full text |Cite
|
Sign up to set email alerts
|

Mineralocorticoid receptor blockade confers renoprotection in preexisting chronic cyclosporine nephrotoxicity

Abstract: Recent studies from our laboratory have shown that the mineralocorticoid receptor (MR) blockade with spironolactone (Sp) prevented renal dysfunction and reduced renal injury in both acute and chronic cyclosporine (CsA) nephrotoxicity. This study was designed to evaluate whether Sp administration reduces functional and structural renal damage associated in the setting of preexisting chronic CsA nephrotoxicity. Twenty eight male Wistar rats were fed a low-sodium diet. Fourteen received vehicle (V) and the others… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
82
0
4

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 99 publications
(93 citation statements)
references
References 49 publications
7
82
0
4
Order By: Relevance
“…Some strategies, like antifibrotic agents, were able to improve renal structural damage but had no beneficial effect on renal function. In contrast, strategies such as L-arginine (5,57) and spironolactone (20,43,44), which improved renal function probably due to an effect on vascular resistances, had an additional beneficial effect on structural injury, suggesting that the increase in vascular resistances, with consequent renal ischemia, seems to be a major pathophysiological mechanism involved in the development of structural injury. In this regard, we propose that aldosterone plays a central role in the establishment of renal dysfunction and structural injury observed in chronic CsA nephrotoxicity (Fig.…”
Section: A New Scheme Of Csa-induced Nephrotoxicitymentioning
confidence: 97%
See 1 more Smart Citation
“…Some strategies, like antifibrotic agents, were able to improve renal structural damage but had no beneficial effect on renal function. In contrast, strategies such as L-arginine (5,57) and spironolactone (20,43,44), which improved renal function probably due to an effect on vascular resistances, had an additional beneficial effect on structural injury, suggesting that the increase in vascular resistances, with consequent renal ischemia, seems to be a major pathophysiological mechanism involved in the development of structural injury. In this regard, we propose that aldosterone plays a central role in the establishment of renal dysfunction and structural injury observed in chronic CsA nephrotoxicity (Fig.…”
Section: A New Scheme Of Csa-induced Nephrotoxicitymentioning
confidence: 97%
“…Thus our findings in acute and chronic models of CsA nephrotoxicity indicated that spironolactone is an effective prophylactic agent to prevent the development of CsA nephrotoxicity. Finally, Perez-Rojas et al (43) analyzed whether spironolactone blockade can contribute to prevent the progression of existing tubulointerstitial injury and renal dysfunction in the model of chronic CsA nephropathy. As shown in Fig.…”
Section: Role Of Aldosterone In Csa Nephrotoxicitymentioning
confidence: 99%
“…The validation studies showed a significant correlation (92%) between the ELISA and microbead-based assay. This assay has been used to determine urinary levels of Kim-1 in several recent studies using rat models (de Borst et al, 2007;Perez-Rojas et al, 2007;van Timmeren et al, 2006). …”
mentioning
confidence: 99%
“…The renoprotective effects of spironolactone or epleronone had been seen in many other animal models of renal injury not limited to diabetic nephropathy, as noted in a recent review by Nishiyama et al (46) These models included streptozotocin-induced and other forms of diabetic rats and mice, obese SHR rats, murine lupus nephritis, unilateral ureteral obstruction, ischemia reperfusion injury, 5/6 th nephrectomised rats and rats treated with AngII infusion, NO synthase inhibitor or cyclosporine (53)(54)(55)(56)(57)(58)(59)(60)(61)(62)(63)(64)(65)(66). In these animal models, treatment with aldosterone blockers had no effect on systemic blood pressure.…”
Section: Aldosterone Biology and Lessons Learnt From Animal Modelsmentioning
confidence: 95%